A new zeolitic lithium aluminum imidazolate framework. Issue 23 (2nd June 2021) - Jiang, Guangshen; Bon, Volodymyr; Xu, Fei; Garai, Bikash; Zhang, En; Senkovska, Irena; Poetke, Stephanie; Hippauf, Felix; Hausdorf, Steffen; Paasch, Silvia; Brunner, Eike; Wang, Hongqiang; et al.
Abstract : Lithium aluminum hydride reacts with 2-methylimidazole through dehydrogenation to form a new aliovalent mixed-metal zeolitic framework DUT-174 [LiAl(2-methylimidazolate)4 ] n . Abstract : An aliovalent mixed-metal framework DUT-174 [LiAl(2-methylimidazolate)4 ] n, isostructural to ZIF-8, was synthesized from lithium aluminum hydride (LiAlH4 ) and 2-methylimidazole (2-mImH) through dehydrogenation. Lithium and aluminum cations acting as alternating framework nodes are coordinated tetrahedrally by (2-mIm) - . DUT-174 has a high specific surface area of 1149 m 2 g −1 and CO2 uptake of 11.57 mmol g −1 at 195 K.